2013
DOI: 10.1007/s00520-013-1720-z
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the treatment of post-chemotherapy chronic fatigue: a randomized, blinded, sham-controlled trial

Abstract: Purpose Many cancer patients experience persistent fatigue after the completion of chemotherapy. A previous single-arm study provided evidence for an effect of acupuncture in this population. We conducted a randomized controlled trial to determine whether acupuncture reduces post-chemotherapy chronic fatigue more effectively than sham acupuncture. Methods Cancer patients reporting significant fatigue persisting for at least 2 months following the completion of chemotherapy were randomized to receive once wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 16 publications
1
79
0
5
Order By: Relevance
“…All studies were RCTs of parallel design. Five trials had 2 study groups, [22][23][24][25][26] and 2 trials had 3 study groups. 27,28 Risk of bias assessment has been completed elsewhere for these trials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were RCTs of parallel design. Five trials had 2 study groups, [22][23][24][25][26] and 2 trials had 3 study groups. 27,28 Risk of bias assessment has been completed elsewhere for these trials.…”
Section: Resultsmentioning
confidence: 99%
“…To recruit patients with persistent CRF, studies sought patients who had chemotherapy at least 1 month [24][25][26][27][28] or at least 60 days prior to the trial commencement date. 22 One study did not include length of time since chemotherapy or radiotherapy. 23 The type of chemotherapy was documented in all 3 Molassiotis studies and length of chemotherapy regime or radiotherapy in one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both true and sham acupuncture were found to alleviate fatigue slightly, but there were no significant differences between the two groups [12]. However, a 2007 randomized trial demonstrated that true acupuncture showed substantial improvement (36%) in fatigue levels compared with sham acupuncture and acupressure [13].…”
Section: Postchemotherapy Chronic Fatiguementioning
confidence: 97%